A Transitivity Analysis of Reading Passages in The Textbook Bahasa Inggris for Grade XI - Ariany Restu Kurnia Santi; Siti Mukminatun (Lingua Pedagogia, 2023)
This research aimed to analyze the experiential meaning in reading passages found in the Bahasa Inggris for Grade 11 textbook in Indonesia. The research based its analyses on theory of Transitivity System. This research has two objectives, namely, 1) to describe the process types, participants and circumstances dominantly used in each clause within the texts existed in the Bahasa Inggris, and 2) to identify whether the processes reflect the linguistic feature choices of genre provided in textbook Bahasa Inggris. In conducting this research, a qualitative content analysis method was employed. Two data sheets were used as the main instrument. The data were from seven reading passages in the textbook. They were then broken down into clauses. In collecting the data, this research applied document analysis. The data analysis was done in three phases; data reduction (data condensation), data display and conclusion drawing/verifying. There are six process types found in 639 clauses in seven reading passages in the Bahasa Inggris textbook. The findings show the frequency and percentage of each process type as follows: Material Process was 331 (49%), Mental Process was 73 (11%), Relational Process was 149 (22%), Behavioral Process 37 (5%), Verbal Process was 77 (11%), and Existential Process was 15 (2%). It is found that the most dominant used is Material Process which reflects the idea that clauses through which experiences and phenomenon are represented are dominated by entities of actions or something that happened physically. While, the least used is Existential Process. The findings indicate that the processes have reflected the linguistic feature choices of genre in the Bahasa Inggris textbook.